The Tibetan Book of Living and Dying - Panyawutho, PhraSamuBanjong; Leeka, Jaras (Journal of Graduate MCU KhonKaen Campus, 2023)
This book review aims to present the Tibetan teachings of preparing for death and helping dying persons. It is a learning process from the death that will come with all human beings. Death is simply a transition from one state to another one. When humans understand this natural condition, they lead a life of carelessness and no fear of death.Keywords: The Ocean; Tibetan Teachings; Preparing for Death